Fatty acid composition and metabolic partitioning of α-linolenic acid are contingent on life stage in human CD3+ T lymphocytes - West, Annette L.; von Gerichten, Johanna; Irvine, Nicola A.; Miles, Elizabeth A.; Lillycrop, Karen A.; Calder, Philip C.; Fielding, Barbara A.; Burdge, Graham C. (Frontiers in Immunology, 2022)
Immune function changes across the life course; the fetal immune system is characterised by tolerance while that of seniors is less able to respond effectively to antigens and is more pro-inflammatory than in younger adults. Lipids are involved centrally in immune function but there is limited information about how T cell lipid metabolism changes during the life course. We investigated whether life stage alters fatty acid composition, lipid droplet content and α-linolenic acid (18:3ω-3) metabolism in human fetal CD3+ T lymphocytes and in CD3+ T lymphocytes from adults (median 41 years) and seniors (median 70 years). Quiescent fetal T cells had higher saturated (SFA), monounsaturated fatty acid (MUFA), and ω-6 polyunsaturated fatty acid (PUFA) contents than adults or seniors. Activation-induced changes in fatty acid composition that differed between life stages. The principal metabolic fates of [13C]18:3ω-3 were constitutive hydroxyoctadecatrienoic acid synthesis and β-oxidation and carbon recycling into SFA and MUFA. These processes declined progressively across the life course. Longer chain ω-3 PUFA synthesis was a relatively minor metabolic fate of 18:3ω-3 at all life stages. Fetal and adult T lymphocytes had similar lipid droplet contents, which were lower than in T cells from seniors. Variation in the lipid droplet content of adult T cells accounted for 62% of the variation in mitogen-induced CD69 expression, but there was no significant relationship in fetal cells or lymphocytes from seniors. Together these findings show that fatty acid metabolism in human T lymphocytes changes across the life course in a manner that may facilitate the adaptation of immune function to different life stages.